(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Researchers indicated that university students’ engagement is not to the expected level. The lacks of engagement among students have societal and individual cost. One of the cost is failure to succeed in academic work. The purpose of the present study was to investigate the status of university students’ engagement and to assess the relationship between university students’ engagement and academic achievement. To arrive at the stated objective, causal- correlation design was employed .Multi stage sampling was used to select and a sample of 530 students from three universities among second and third year batches were taken as a sample. Descriptive statistics such as mean and standard deviation and, regression analysis were used to analyze the data. The study found that mean score of emotional and cognitive engagement were found to be below the average. In addition, the relationship between university students’ engagement and their academic achievements were found to be positively correlated. Specifically, behavioral engagement of students contributed strongest and unique in explaining of academic achievements. Conclusions were drawn based on the finding of the study.